Synthesis of SiO2-coated Bi2S3/poly(styrene) nanocomposites by in-situ polymerization - Esteves, A. C. (2006)
New nanocomposites containing silica-coated Bi2S3 nanofibers were synthesised by in situ polymerization using two distinct synthetic strategies: emulsion and suspension polymerization. Transmission and scanning electron microscopy of the nanocomposite particles showed that in both cases the Bi2S3/SiO2 nanoparticles were densely coated with poly(styrene). In situ emulsion polymerization afforded nanocomposites in which the nanofibers were coated with polymer spheres whilst suspension polymerization gives rise to a homogeneous polymer layer coat. The morphology of the poly(styrene) coating observed is discussed considering the surface modification of the nanofibers and the polymerization technique involved.